Abuse and exploitation of doctoral students: a conceptual model for traversing a long and winding road to academia - Cohen, Aaron (Journal of business ethics, 2022)
This paper develops a conceptual model of PhD supervisors’ abuse and exploitation of their students and the outcomes of that abuse. Based on the literature about destructive leadership and the "dark side" of supervision, we theorize about why and how PhD student abuse and exploitation may occur. We offer a novel contribution to the literature by identifying the process through which PhD students experience supervisory abuse and exploitation, the various factors influencing this process, and its outcomes. The proposed model presents the Dark Triad, perceptions of goal blockage, and perceptions of ethical culture as potential characteristics of the PhD supervisor and implies the mediation of the perceptions of power and politics in the relationship between the Dark Triad and student abuse and exploitation. Institutional policies and practices concerning doctoral students and their characteristics are proposed as moderators in such a relationship. Finally, the model suggests that student abuse and exploitation may hinder or even end students’ academic careers. The manuscript discusses the theoretical and practical contributions and managerial implications of the proposed model and recommends further exploration of the dark sides of academia.